Comparison of Treatment Efficacy in Migraine treated with Nortriptyline and Caffeine Cessation vs Nortriptyline without Caffeine Cessation - Muhammad Imtiaz, Faheem Saeed, Shafia Tufail, Namra Tufail, Anam Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The usage of caffeine as a psychostimulant is prevalent worldwide. However, consuming excessive amounts of caffeine can result in various acute and chronic biological and physiological alterations, which can lead to symptoms such as cognitive impairment, depression, fatigue, insomnia, cardiovascular changes, and headaches. Aim: The objective of this study was to compare the treatment efficacy in migraine patients treated with nortriptyline and caffeine cessation versus nortriptyline without caffeine cessation. Method: It’s a randomized controlled trial. Research was conducted at Department of Neurology, Sir Ganga Ram Hospital Lahore. This study involved 76 patients of both genders, aged between 18-60 years diagnosed with migraine within the past 6 months which were randomly divided into two treatment groups. Patients in both the groups received nortriptyline. However, those in the experimental group were also advised to avoid caffeine intake. Results: The outcome variable was the efficacy of treatment which was labeled if the patient had ≤1 episode of headache/week after 4 weeks of treatment. The mean age of the patients was 33.5±12.3 years. There were 27 (35.5%) male and 49 (64.5%) female patients. The frequency of treatment efficacy was significantly higher in patients treated with nortriptyline and caffeine cessation as compared to those treated with nortriptyline without caffeine cessation (78.9% vs. 39.5%; p-value<0.001). In our current practice we don’t prohibit caffeine use during treatment of patients with migraine which might be a cause for treatment failure and patient’s dissatisfaction. If the results of the present study reveal that caffeine 14 cessation may improve treatment outcome of migraine patients, it will enable better management of such patients presenting in future clinical practice. Conclusion: In the present study, caffeine cessation was found to be associated with a significantly higher frequency of treatment efficacy among patients receiving nortriptyline for migraine regardless of patient’s age, gender, BMI, duration of disease, and number of headache episodes per week before the start of treatment which necessitates that caffeine cessation should be advised in such patients to improve the treatment response in future clinical practice. Keywords: Migraine, Nortriptyline, Caffeine Cessation, Headache, Nortriptyline, neurological disorder